The influence of pre-treatment methods and matrix effect on sesame (Sesamum indicum) sandwich ELISA detection. Issue 1 (1st January 2021) - Wang, Junyu; Li, Wenjie; Wang, Yaqing; Pavase, Tushar; Zhang, Jiukai; Li, Zhenxing; Lin, Hong
ABSTRACT: Food allergy is a serious health risk and severely affects the quality of life in individuals all over the globe. In recent years, there has been an evident increase in the number of food allergy cases due to the consumption of sesame. Hence, to develop a robust and reliable detection method for sesame allergen has become a high priority. In this research, a sandwich ELISA method was established to detect sesame allergens using rat and rabbit antiserums. The limit of detection for sandwich ELISA was estimated at 1 ng/mL, revealing high sensitivity. At the same time, it was found that the most suitable pre-treatment extract for this method was 0.1 M, pH 9.6 Na2 CO3 -NaHCO3 containing 0.5% SDS. This sandwich ELISA method can sensitively and efficiently detect foods containing sesame ingredients, which can protect the sensitive individuals from the exposure to sesame allergenic foods.